Awake Fibreoptic Intubation in the Sitting Position in a Patient with a Huge Goitre - Kirti Nath Saxena; Sudhir Kumar; Bharti Taneja; Prachi Gaba (Case Reports in Anesthesiology)
A 46-year-old woman was anesthetized for total thyroidectomy. The thyroid was massive, deviating the trachea to the right and causing attenuation of the trachea radiologically. She had symptoms of respiratory obstruction in the supine position. Awake FOB-guided intubation was done in sitting position after airway topicalisation, and the airway was intubated with difficulty with 7.0 mm cuffed orotracheal tube. We describe this case in detail and discuss the significance of careful approach to planning and preparation in the management of such a case.